2015
DOI: 10.1021/jacs.5b04324
|View full text |Cite
|
Sign up to set email alerts
|

Monoselective o-C–H Functionalizations of Mandelic Acid and α-Phenylglycine

Abstract: Pd-catalyzed C–H functionalization of mandelic acid and α-phenylglycine is reported. We have developed different protocols for the arylation, iodination, acetoxylation, and olefination of these substrates based on two different (Pd(II)/Pd(IV) and Pd(II)/Pd(0)) catalytic cycles. Four crucial features of these protocols are advantageous for practical applications. First, the α-hydroxyl and amino groups are protected with simple protecting groups such as acetates (Ac, Piv) and carbamates (Boc, Fmoc), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 71 publications
2
49
0
Order By: Relevance
“…The best conversions were obtained using hexafluoroisopropanol (HFIP). [36] The amount of catalyst Pd(OAc) 2 was reduced to 5 mol % with just a slight decrease of conversion to 3 a (Table 1, entry 17). The optimized reaction conditions were Pd(OAc) 2 (5 mol %) as the catalyst, 1.5 equiv of the aryl halide 2, AgOAc (1.3 equiv) as the base in HFIP at 110 8C.…”
Section: Resultsmentioning
confidence: 99%
“…The best conversions were obtained using hexafluoroisopropanol (HFIP). [36] The amount of catalyst Pd(OAc) 2 was reduced to 5 mol % with just a slight decrease of conversion to 3 a (Table 1, entry 17). The optimized reaction conditions were Pd(OAc) 2 (5 mol %) as the catalyst, 1.5 equiv of the aryl halide 2, AgOAc (1.3 equiv) as the base in HFIP at 110 8C.…”
Section: Resultsmentioning
confidence: 99%
“…The redox‐neutral C−H arylation of arylacetic acids has been slow to develop. In 2015, Yu and co‐workers described the Pd(OAc) 2 ‐catalyzed ortho ‐arylation of mandelic acid derivatives by using aryl iodides as part of a thorough study of multiple C−H functionalization reactions of these substrates . The reaction conditions were mild enough to tolerate various sensitive functional groups, while yielding only monosubstituted products without epimerization of the vulnerable chiral center.…”
Section: C−c Bond Formationmentioning
confidence: 99%
“…Ligand‐enabled Fujiwara–Moritani reactions have also been successfully applied to the olefination of mandelic acid. The selectivity mono‐ vs. disubstitution could be modulated by prolonging the reaction time without leading to racemization . From a detailed mechanistic study of C−H olefination of arylacetic acids, the authors concluded that the addition of an appropriate amino acid ligand triggers a switch in mechanism from C−H bond cleavage by electrophilic palladation to proton abstraction, which was the key toward better reactivity and selectivity .…”
Section: C−c Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, consistent with the known influence of steric effects in the site selectivity of many C À H functionalizations, [22] the introduction of a substituent at the benzylic position in both substrates allowed a very high monoalkenylation reaction while improving the yield (9 and 10, 87% and 74%, respectively, entries 4 and 5). Remarkably, in contrast to the majority of reported C À H alkenylation reactions for which the diolefination of substrates bearing two equivalent ortho-C À H bonds is a persistent problem, [23] this approach allowed for facile and high yielding formation of the monoalkenylated products of benzyl and phenethyl 2-pyridyl sulfones with excellent ortho-regiocontrol and mono-/disubstitution selectivity using 1.1 equiv, of the alkene. [24] The key directing role of the (2-pyridyl)sulfonyl unit was established through a control experiment showing the complete lack of reactivity of the related benzyl phenyl sulfone (1b) when submitted to the reaction with phenyl vinyl sulfone under otherwise identical reaction conditions to those in Table 1, the reaction leading to exclusive recovery of starting material even after a prolonged time (Scheme 2).…”
mentioning
confidence: 99%